2015
DOI: 10.18203/2349-3291.ijcp20150990
|View full text |Cite
|
Sign up to set email alerts
|

Clinicoetiological profile and risk assessment of newborn with respiratory distress in a tertiary care centre in South India

Abstract: First breath is the most vital parameter in the beginning of a new life. Respiratory distress (RD) is among the most common symptom complexes seen in newborn infants. A variety of respiratory and non-respiratory disorders manifest clinically as respiratory distress. This study was undertaken with the aim to know the most common etiological factors responsible for neonatal respiratory distress and effect of modern advancements like bubble CPAP and mechanical ventilation on the outcome of newborns with severe di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…It was similar to previous studies The male to female ratio was 1.1:1 among cases. The results were similar to the study done by Sodawat et al, Sahoo et al, Nagendra et al, Brahmaiah, et al[10][11][12][13][14][15][16][17] Most new-borns had mild to moderate severity (82.5%) of respiratory distress. The study done by Brahmaiah (81%) and Sahoo et al (83%) showed similar results 10,17.…”
supporting
confidence: 90%
“…It was similar to previous studies The male to female ratio was 1.1:1 among cases. The results were similar to the study done by Sodawat et al, Sahoo et al, Nagendra et al, Brahmaiah, et al[10][11][12][13][14][15][16][17] Most new-borns had mild to moderate severity (82.5%) of respiratory distress. The study done by Brahmaiah (81%) and Sahoo et al (83%) showed similar results 10,17.…”
supporting
confidence: 90%
“…In a recent study done by Sahoo MR et al death occurred in 11.1% cases of RD. 19 Mortality was seen in 24.13% newborns of HMD, 11.11% of newborns with MAS, 9.09% of newborns with congenital pneumonia.…”
Section: Discussionmentioning
confidence: 97%